Influence of rheology and geometry on the teapot effect of a curtain coater - Döll, Harald; Gerlach, Daniel; Alleborn, Norbert; Delgado, Antonio (European Physical Journal - Special Topics, 2009)
The present study investigates the deflection of a liquid sheet forming at the die lip of a slide-fed curtain coater, known as 'teapot effect'. The influence of the shear-rate dependent viscosity, the geometry ofthe lip edge and the flow rate on the degree of deflection has been considered. © EDP Sciences and Springer 2009.
UnivIS-Import:2015-03-09:Pub.2009.tech.ITC.stmmec.influe_0